2012
DOI: 10.1111/j.1752-7325.2012.00312.x
|View full text |Cite
|
Sign up to set email alerts
|

Wealth effect and dental care utilization in the United States

Abstract: Objective The purpose of this article is to examine the relationship of wealth and income and the relative impact of each on dental utilization in a population of older Americans, using data from the Health and Retirement Study (HRS). Methods Data from the Health and Retirement Study (HRS) were analyzed for U.S. individuals aged 51 years and older during the 2008 wave of the HRS. The primary focus of the analysis is the relationship between wealth, income and dental utilization. We estimate a multivariable m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 19 publications
0
48
0
1
Order By: Relevance
“…9,13,32,33 Nonpoor older adults were more likely to obtain dental care than were poor older adults, and older adults with private dental insurance were more likely to obtain dental care than were those without dental insurance. However, dental care utilization among older adults enrolled in Medicaid was not different from those without dental insurance, even though Ohio is one of 28 states whose Medicaid programs provide adult enrollees with dental coverage beyond emergency treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,13,32,33 Nonpoor older adults were more likely to obtain dental care than were poor older adults, and older adults with private dental insurance were more likely to obtain dental care than were those without dental insurance. However, dental care utilization among older adults enrolled in Medicaid was not different from those without dental insurance, even though Ohio is one of 28 states whose Medicaid programs provide adult enrollees with dental coverage beyond emergency treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Study results indicate lower dental care utilization is associated with being male and of a minority race and having a lower level of education, lower income, lack of dental insurance, a rural residence and cognitive impairment. 9–12 In 2012, Manski and colleagues 13 analyzed dental care utilization and the relevant individual factors among older adults aged 51 years or older by using data from the 2008 wave of the National Institute on Aging’s Health and Retirement Study. They found that older adults with dental insurance were 2.3 times more likely to have dental visits during the two year period preceding the survey than were those without dental insurance.…”
mentioning
confidence: 99%
“…This is relevant, since schooling was a factor associated with UDHS, probably because lack of education makes it difficult to obtain a formal paid employment and therefore have limited access to dental health services. [27][28][29] Another associated factor was being a beneficiary of the "Programa Oportunidades", one of the most important programs in the country, which includes among its benefits, dental care. However, only one third of the PW and OA have such support.…”
Section: Discussionmentioning
confidence: 99%
“…We selected gender, age and family income as adjustment factors as these factors have been reported to be associated with regular dental attendance [2,4,[6][7][8][9][10][11]. Moreover, work environment [14,15], lifestyle [16][17][18] and oral hygiene behaviour [19,20] were included as questionnaire components because these factors have been reported as factors associated with dental diseases or regular dental attendance.…”
Section: Questionnaire Componentsmentioning
confidence: 99%
“…Although gender, age and income have been reported as associated factors with regular dental attendance [2,4,[6][7][8][9][10][11], few reports have discussed a relationship between work environment, lifestyle and oral hygiene behaviour. Factors such as gender, age and income are difficult to control.…”
Section: Introductionmentioning
confidence: 99%